1988
DOI: 10.1083/jcb.107.3.1215
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin and vitronectin regulate the organization of their respective Arg-Gly-Asp adhesion receptors in cultured human endothelial cells.

Abstract: Abstract. Human umbilical vein endothelial cells (ECs) adhere in vitro to proteins of the extracellular matrix including fibronectin (fn) and vitronectin (vn). Specific receptors for fn and vn have been previously characterized. These receptors belong to a family of membrane glycoproteins characterized (a) by being a transmembrane complex of two noncovalently linked subunits and (b) by recognizing the tripeptide ArgGly-Asp on their respective ligands. In this paper we investigated how vn and fn control the org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
121
1

Year Published

1992
1992
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(131 citation statements)
references
References 34 publications
9
121
1
Order By: Relevance
“…For instance, fibronectin and vitronectin have been proposed to organize and cluster preexposed receptor molecules freely moving within the plane of the membrane of endothelial cells in the correspondence of adhesion plaques [21]. Furthermore, in a recent study, Bowditch et al [22] have shown the importance of sequences in fibronectin other than the RGD tripeptide main site that interact with integrin aabj3.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, fibronectin and vitronectin have been proposed to organize and cluster preexposed receptor molecules freely moving within the plane of the membrane of endothelial cells in the correspondence of adhesion plaques [21]. Furthermore, in a recent study, Bowditch et al [22] have shown the importance of sequences in fibronectin other than the RGD tripeptide main site that interact with integrin aabj3.…”
Section: Discussionmentioning
confidence: 99%
“…FN contains several discrete domains that are involved in the binding to cell surfaces, including the C-terminal Hep II domain, 17,18 the alternatively spliced type III connecting segment, 19 and the central cell-binding domain. 20 EC adhesion to FN is primarily mediated by ␣5␤1, 21 but also by proteoglycans on the cell surface. A chondroitin sulfate proteoglycan with weak affinity for FN reduced binding of FN to both cells and the purified FN receptor (␣5␤1), probably by steric hindrance.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that there is remarkable specificity in recruitment of integrins to focal adhesions (11,12). This specificity was manifest in these experiments by the failure of Ottrd33 to enter focal adhesions formed during adhesion to fibronectin.…”
Section: Discussionmentioning
confidence: 99%